2022
DOI: 10.1177/21582440221102438
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship in Tourism Studies in the 21st Century: A Bibliometric Study of Wos and Scopus

Abstract: Entrepreneurship and tourism are linked as relevant aspects of study due to their influence on the society’s development. In attempt to identify the main theoretical contributions in the 21st century, a bibliometric study was carried out, based on publications of tourism entrepreneurship in the Web of Science (WoS) and Scopus databases. As a result, data from 268 documents were obtained and processed in VosViewer. The main findings place Haber, Altinay, and Hallak as the most cited authors; when analyzing co-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…This result suggests that sustainable education in tourism universities requires more research, as few academics have addressed it (Leo´n-Go´mez & Mora Forero, 2022). Therefore, more researchers should consider contributing to the current debate (Camargo & Gretzel, 2017;Ochoa Jime´nez et al, 2022;Sharma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that sustainable education in tourism universities requires more research, as few academics have addressed it (Leo´n-Go´mez & Mora Forero, 2022). Therefore, more researchers should consider contributing to the current debate (Camargo & Gretzel, 2017;Ochoa Jime´nez et al, 2022;Sharma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many articles address the environmental perspective of tourism (S. Liu & Li, 2020;Moyle et al, 2021;Seguı´-Amortegui et al, 2019;C. Zhang, Xu, et al, 2022), but few have analysed the educational perspective of this relationship (Ochoa Jime´nez et al, 2022;Sharma et al, 2021). As a result, there is growing concerned about the need to teach sustainability within the curricula of tourism universities (Leo´n-Go´mez & Mora Forero, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Such training must be done with patience, perseverance, full of empathy, a friendly manner, and encouragement, reflecting the characteristics of social entrepreneurship [52]. The PwSAs took approximately three years to complete the doormat-making training program, then produce the doormats in their homes.…”
Section: Entrepreneuring Pwsas Before and During The Pandemicmentioning
confidence: 99%
“…b stands for intercept, x n is the independent variable, a is the coefficient of the independent variable, 𝜀 is the random perturbation term. Considering that the units of variables are inconsistent, the logarithms of independent and dependent variables are taken, respectively, to obtain formula (7):…”
Section: Construction Of Relationship Modelmentioning
confidence: 99%
“…Correspondingly, the amount of published literature on professional educational media is the equal interpretation of hot topics of public concern. As an essential window for scientific research achievements and academic exchanges, all professional academic platforms can actively pay attention to and grasp the focus and difficulties of scientific and technological research and timely reflect on the hot spots and public needs in various stages of society 7 . Based on relevant literature on professional academic platforms, some scholars have found that the research hot‐spots of Chinese middle school geography textbooks mainly focus on seven aspects: comparison of geography textbooks, textbook system, textbook optimization, textbook analysis and redevelopment, infiltration of geographical thought, books and courses, and development and practice of local texts 8 .…”
Section: Introductionmentioning
confidence: 99%